2023
DOI: 10.1371/journal.ppat.1011217
|View full text |Cite
|
Sign up to set email alerts
|

Fusogenic structural changes in arenavirus glycoproteins are associated with viroporin activity

Abstract: Many enveloped viruses enter host cells by fusing with acidic endosomes. The fusion activity of multiple viral envelope glycoproteins does not generally affect viral membrane permeability. However, fusion induced by the Lassa virus (LASV) glycoprotein complex (GPc) is always preceded by an increase in viral membrane permeability and the ensuing acidification of the virion interior. Here, systematic investigation of this LASV fusion phenotype using single pseudovirus tracking in live cells reveals that the chan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 75 publications
2
3
0
Order By: Relevance
“…Unlike influenza viruses, arenaviruses do not have proton channels in their lipid envelope that actively acidify the virion upon endocytosis. However, it has recently been shown for LASV that protons passively cross the viral membrane, which leads to acidification of the virus interior prior to membrane fusion. , Similar observations have been reported for Ebola virus, where acidification of virions leads to viral matrix reorganization . Besides the pH-dependent NP–Z interaction, we observed that Z starts to oligomerize between pH 5 and 5.5.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Unlike influenza viruses, arenaviruses do not have proton channels in their lipid envelope that actively acidify the virion upon endocytosis. However, it has recently been shown for LASV that protons passively cross the viral membrane, which leads to acidification of the virus interior prior to membrane fusion. , Similar observations have been reported for Ebola virus, where acidification of virions leads to viral matrix reorganization . Besides the pH-dependent NP–Z interaction, we observed that Z starts to oligomerize between pH 5 and 5.5.…”
Section: Discussionsupporting
confidence: 89%
“…A potentially important factor could be the pH, as LASV is taken up via the endosomal pathway. It was recently shown that acidification of Lassa virions occurs before membrane fusion via reorganization of the glycoprotein complex. , A low pH could lead to the dissociation of RNPs from the Z protein lining the inner side of the viral membrane. Therefore, we evaluated the pH-dependence of the NP–Z interaction by incubating the proteins at varying pH values between 5 and 7.5 and subsequently measured NP–Z complex formation by nMS (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Based on these results ( Fig. 7 to 9 ) and those of others ( 26 , 35 , 36 ), we suggest K + influences interactions between internal Z matrix and RNPs ( Fig. 10 ).…”
Section: Resultssupporting
confidence: 66%
“…As the GPC-CD164 interaction at low pH is known to promote membrane fusion ( 19 ), we reasoned K + may exert its influence on uncoating by one of three options: (i) by modulating the interaction between external virion component GP1 and its CD164 ligand; (ii) by modulating GPC-CD164-mediated membrane fusion; or (iii) by influencing separation between internal virion components such as RNP and Z (i.e., uncoating). This latter possibility is particularly intriguing, considering a similar mechanism proposed for influenza virus ( 26 ) and the recent demonstration that the arenavirus interior is accessible to ion influx via formation of a glycoprotein-associated envelope pore in response to low pH ( 35 , 36 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation